EFFECT OF BANK IMAGE AND PERCEPTION OF VALUE OF FINANCING CONSUMPTIVE CUSTOMER LOYALTY IN ISLAMIC BANK MANDIRI BRANCH PADANG - V Annora, Vebby; Amaluis, SE,MM, Dina; Susanti, Spd.Msi, Nora (Pendidikan Ekonomi, 2014)
Abstract The purpose of study was to analyze the effect of the banks image and perception of value on customer loyalty in the consumer finance Syariah Mandiri Bank Branch Padang . The methodology used in this study is the method of multiple linear regression analysis. First results showed that: The image bank and a not significant effect on customer loyalty in the consumer finance Syariah Mandiri Bank Branch Padang is indicated by a coefficient of 0.020 with significant value of 0,817 < α = 0.05. Second: The perception of the value of a positive and significant effect on customer loyalty in the consumer finance Syariah Mandiri Bank Branch Padang is indicated by a coefficient of 0.913 with significant value of 0.000 < α = 0.05 Third: The image and perception of the value of the bank jointly effect on customer loyalty in the consumer finance Syariah Mandiri Bank Main Branch Padang indicated by the F - statistic of 150.161, with a significant value of 0.000 < α = 5 %, and the R - squared value of 0.756, which means 75,6 % of customer loyalty is influenced by Image Bank and Perception Value while the rest is explained by other variables